Effect of topical nitric oxide donors 0.03% nitroglycerin and 0.1% hydralazine on intraocular pressure in healthy canine eyes. Issue 6 (22nd September 2022) - Wilcox, Parker A.; Strong, Travis D.; Sebbag, Lionel; Allbaugh, Rachel A.
Abstract: Objective: To investigate the potential intraocular pressure (IOP)‐lowering effects of nitric oxide (NO)‐donating compounds in healthy canine eyes Methods: A total of 79 dogs were divided into 3 groups in a masked, controlled and randomised study. Group N ( n = 26) was administered 0.03% nitroglycerin in one eye and vehicle‐control in the other, Group H ( n = 26) was administered 0.1% hydralazine in one eye and vehicle‐control in the other, while Group C ( n = 27) received vehicle‐control in both eyes (control group). Following eye drop administration, IOP was measured in both eyes at selected times (10–250 min), along with monitoring of heart rate and signs of ocular discomfort. Data was analysed with repeated measures mixed model and one‐way ANOVA Results: IOP was significantly reduced over the 4‐h period with 0.03% nitroglycerin ( p < 0.0001) but not 0.1% hydralazine ( p = 0.520) when compared to contralateral vehicle‐controlled eyes. IOP was reduced by up to 12% with 0.03% nitroglycerin from 10 to 70 min post‐treatment; however, differences in IOP at individual time points were not statistically significant for either drug ( p ≥ 0.133) as compared to contralateral vehicle‐control eyes. No treatment group significantly affected heart rate (compared to Group C), and both treatment groups appeared well tolerated Conclusions: Both compounds were well‐tolerated in healthy dogs. Nitroglycerin mildly reduced IOP in canine eyes, and further investigations are warranted in healthy and diseased states (e.g. glaucoma, ocular hypertension). Abstract : Topical nitric‐oxide donors 0.03% nitroglycerin and 0.1% hydralazine were investigated for the potential effect on intraocular pressure in normal canine eyes. This study determined healthy canine eyes that received 0.03% nitroglycerin had a significantly lower IOP over the 4‐hour testing period when compared to vehicle‐control eyes, although the maximal IOP reduction was somewhat limited (12%). No significant reduction in IOP was identified at any time point in eyes that received 0.1% hydralazine.